POTENSI DAN TINGKAT PEMANFAATAN SUMBERDAYA IKAN DEMERSAL DI PERAIRAN PULAU AMBON PROVINSI MALUKU - Donald Noija; Sulaeman Martasuganda; Bambang Murdiyanto; Am Azbas Taurusman (Jurnal Teknologi Perikanan dan Kelautan, 2014)
One of the fishery resources that have high economic value are demersal fisheries resources in deep sea waters. The results ofthis study found 22 demersal fish species with high economic value captured by fishermen. The results ofthe study found as many as 22 species, five fish stretcher 5 that can be foundin nearly all areas and fishing season. Five types of fish are: lencam (Lethrinus sp.), kurisi (Etelis spp), kerapu (Ephinephelus sp), red snapper (Lutjanus spp), bubara fish (Caranx sp). The types of fish catches were found spread around the waters of Ambon Island. The potential at Maxsimum sustainable Yield (MSY) of fish grouper (Epinephelus spp) 572.02 with 15.75 tonnes optimum effort trip. The average production of 178.919 tonnes currently. Thus the average utilization rate of groupers currently 31.27% or 68.72% untapped. If it is based on the MSY allowable catch for the fish species is 457.60 tons / year. MSY red snapper (Lutjanus spp) 146.83 wih 2.631 tonnes optimum effort trip. Average production is currently 67.704 tons. Thus the average utilization rate of the red snapper fish is currently 47.47%, or in other words the potential for red snapper untapped 52.52%. If it is based on the MSY allowable catch for the fish species is 117 464 tons / year. MSY bubara fish (Caranx sp) 270.60 tonnes with optimum effort 3630 trip with an average yield of 72.96 tons.